Performance indicators in women`s volleyball Olympics and World Championships (2014-2021) - Giatsis, G. (International Journal of Sports Science & Coaching, 2023)
The aim of this study was to explore the match and technical indicators between winning and losing women's teams in the Olympics and World Championships (2016-2021) depending on the final score of the matches and to compare the winners` technical indicators in 3-set matches to those of men in the respective competitions. A total of 281 volleyball matches were analyzed from the Women's Olympics (2016 and 2021) and World Championships (2014 and 2018). Discriminant function analysis determined which skill(s) contributed significantly to winning matches in every type of score. This study showed that the teams that won 3-0 and 3-1 matches had better performance in all scoring skills (serve, attack, block, and opponent errors) compared to their opponents, while the opponents` errors did not affect the result. In 5-set matches, block points were the main predictor of a team's success. In conclusion, the results of the women's teams at the highest level of volleyball matches, show that different performance indicators determine the match outcome. The attack is not the only skill that increases the probability of winning a match, since block and serve to contribute equally significantly. Furthermore, in 5-set matches, blocking is the technical skill that differentiates the winning from the losing teams. Finally, in 3-set matches, it seems that the performance indicators differ between women and men in attack efficiency, block, and opponent error points.